The impact of cooperative learning on pupils’ peer acceptance and perceptions of peer support - Smith, Helen (2017)
Cooperative Learning, an approach that emphasises positive interdependence and individual accountability in the classroom, has been widely promoted as a pedagogical approach that can enhance not only pupils’ academic outcomes, but also their social outcomes (Johnson & Johnson, 2000). More specifically, research has indicated some potential for Cooperative Learning to impact on pupils’ peer acceptance and perceptions of peer support. Questions remain, however, around a potential differential impact, and the extent to which findings can be generalised to UK, mainstream classes.